Total Hip Replacement in an Ipsilateral Above-the-Knee Amputation: Surgical Technique, Rehabilitation, and Review of the Literature. (March 2013) - Malagelada, Francesc; Coll Rivas, Moisès; Jiménez Obach, Albert; Auleda, Jaume; Guirao, Lluis; Pleguezuelos, Eulogio
In this article, we present a case report of a 62-year-old patient who previously underwent an above-the-knee amputation for vascular disease and we performed a total hip replacement on him because of hip osteoarthritis. As the only postoperative complication, the patient developed a methicillin-resistant Staphylococcus aureus surgical site infection, which was successfully treated. The surgical technique and the postoperative rehabilitation program are described in detail in an attempt to detect and face the challenges that patients with major lower limb amputations may present. The literature is reviewed and all known cases of hip replacements in amputees are presented.